Does Sustainability Awareness Influence Cryptocurrency Preferences? A Study on the Relationship Between Sustainable Development Goals and the Demand for Green vs. Traditional Cryptocurrencies - Juan, Antonio Pérez de; Melero, Iñigo Martín; Gómez-Martínez, Raúl; Medrano-García, María Luisa (Journal of Cultural Analysis and Social Change, 2026)
This study investigates the relationship between public attention to the Sustainable Development Goals (SDGs) and cryptocurrency demand, specifically for Bitcoin (BTC) and Cardano (ADA). Given the environmental concerns associated with Proof-of-Work (PoW) and the sustainability benefits of Proof-of-Stake (PoS), we hypothesize that increased SDG attention leads to higher demand for green cryptocurrencies like Cardano and lower demand for non-green cryptocurrencies like Bitcoin. Using Ordinary Least Squares (OLS) regression and supervised machine learning algorithms, we analyze weekly cryptocurrency returns and Google Trends data from 2020 to 2025. The findings suggest that SDG attention has a statistically significant but weak negative impact on Bitcoin returns, while no significant effect is observed for Cardano. Machine learning models fail to predict cryptocurrency demand effectively. These results indicate that sustainability awareness alone is not a primary driver of cryptocurrency investment behavior.